Motywy stosowania interwencjonizmu kredytowego w rolnictwie - Więznowska, Katarzyna (Motives of Credit Intervention Use for Agriculture, 2005)
Government intervention in agriculture is highly questionable. One instrument of such an intervention are preferential credits. The article presents both justifications for using this instrument in agriculture and the arguments of adversaries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 131-141